2010
DOI: 10.1038/hr.2010.224
|View full text |Cite
|
Sign up to set email alerts
|

Candesartan and amlodipine combination therapy provides powerful vascular protection in stroke-prone spontaneously hypertensive rats

Abstract: The vascular protective effects of placebo, candesartan (1 mg kg À1 per day) monotherapy, candesartan (1 mg kg À1 per day) and amlodipine (1 mg kg À1 per day) combination therapy, and candesartan (1 mg kg À1 per day) and hydrochlorothiazide (HCTZ) (10 mg kg À1 per day) combination therapy for 2 weeks were compared in stroke-prone, spontaneously hypertensive rats. Candesartan monotherapy significantly reduced blood pressure, and both combination therapies were equally and significantly lower than the monotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In primary hypertension, Nox-derived superoxide decreases vascular NO-released from the endothelium resulting in peroxynitrite formation (Dai and Dai 2010). Moreover, vascular gene expression of the NADPH oxidase subunits p22phox, g p91phox, Nox1 and Nox4 are significantly attenuated during hypertension (Takai et al 2011). A recent study also highlights the role played by three single-nucleotide polymorphisms (-930A/G, A640G and C242T) of the p22phox subunit in hypertension (Xaplanteris et al 2010); it was found that the -930A/G, but not the A640G and C242T polymorphism of p22phox is a determinant of peripheral and central pressures in normotensive individuals (Xaplanteris et al 2010).…”
Section: Nox Inhibitors In Hypertensionmentioning
confidence: 99%
“…In primary hypertension, Nox-derived superoxide decreases vascular NO-released from the endothelium resulting in peroxynitrite formation (Dai and Dai 2010). Moreover, vascular gene expression of the NADPH oxidase subunits p22phox, g p91phox, Nox1 and Nox4 are significantly attenuated during hypertension (Takai et al 2011). A recent study also highlights the role played by three single-nucleotide polymorphisms (-930A/G, A640G and C242T) of the p22phox subunit in hypertension (Xaplanteris et al 2010); it was found that the -930A/G, but not the A640G and C242T polymorphism of p22phox is a determinant of peripheral and central pressures in normotensive individuals (Xaplanteris et al 2010).…”
Section: Nox Inhibitors In Hypertensionmentioning
confidence: 99%
“…The levels of MDA, which is a product of lipid peroxidation in tissue extracts, were measured by incubating vascular extracts for 1 h at 60°C with 20 mM thiobarbituric acid in 0.3 mM phosphoric acid (15). The reaction was terminated by cooling on ice, and the mixture was subsequently centrifuged at 15,000 × g for 5 min at 4°C.…”
Section: Dpp-4 Activity and Mda Levelsmentioning
confidence: 99%
“…Isolated rat carotid arteries were cut into 10 × 1.0 mm helical strips and mounted on a myograph under a resting tension of 1.0 g in Tyrode's solution (137 mM NaCl, 2.7 mM KCl, 1.8 mM CaCl 2 , 1.1 mM MgCl 2 , 0.42 mM NaH 2 PO 4 , 12 mM NaHCO 3 , and 5.7 mM glucose, pH 7.4) at 37°C and continuously bubbled with 5% CO 2 / 95% O 2 (15). The strips were initially vasoconstricted with 50 mM KCl, followed by a wash-out of the bathing medium.…”
Section: Acetylcholine-induced Vascular Relaxationmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum ACE activity was measured by incubating plasma for 30 min at 37°C with 5 mM of the substrate hippuryl-His-Leu (Peptide Institute Inc., Osaka) 100 mM phosphate buffer (pH 8.3) containing 300 mM NaCl (18). The reaction was terminated by addition of 3% metaphosphoric acid, and the mixture was subsequently centrifuged at 8,000 × g for 5 min at 4°C.…”
Section: Renin and Ace Activities And Angiotensin II Concentration Inmentioning
confidence: 99%